2004
DOI: 10.1111/j.1553-2712.2004.tb02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Patients to the Emergency Department in a Statewide Database

Abstract: Objectives: To describe the epidemiology of repeat users of the emergency department (ED) using a statewide database. Methods: Probabilistic linkage was used to convert three years of statewide ED visit data into a longitudinal, patientbased data set. Patients were classified as single, repeat (at least two visits within three years), or serial (four or more visits within a 365-day period) users of the ED. Serial patients were further stratified by the number of EDs attended. Descriptive statistics were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 19 publications
3
42
0
2
Order By: Relevance
“…An index attendance was the first ED attendance of a patient defined as one that did not have a prior attendance in the preceding 12 months. The definition of a ‘frequent attender’ was adapted from other studies13 as a patient who attended the ED ≄5 times for any diagnosis. The study included index patients from 1 January to 31 December 2006 (henceforth referred to as the study cohort) who were tracked for re-attendances for 12 months up to 31 December 2007.…”
Section: Methodsmentioning
confidence: 99%
“…An index attendance was the first ED attendance of a patient defined as one that did not have a prior attendance in the preceding 12 months. The definition of a ‘frequent attender’ was adapted from other studies13 as a patient who attended the ED ≄5 times for any diagnosis. The study included index patients from 1 January to 31 December 2006 (henceforth referred to as the study cohort) who were tracked for re-attendances for 12 months up to 31 December 2007.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that a relatively small group of patients account for a disproportionate number of ED visits [5][6][7][8][9]. Moreover, several studies have noted that mental health concerns are prevalent among these service users [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Combined with rising ED visit rates, returning patients to the ED represent a growing problem. A statewide study found that repeat patients compose about two-thirds of ED patients [25]. A study of Belgian psychiatric adult patients examined time to revisit the ED [26] and reported that the majority of patients returned within a few weeks, and younger patients (0 to 44 years) were more likely to return sooner than older patients (45 years and older).…”
Section: Introductionmentioning
confidence: 99%